Structural performance of detachable precast composite column joints with mechanical metal plates. (1st April 2018) - Nzabonimpa, J.D.; Hong, Won-Kee
Highlights: Numerical model was developed to predict mechanical joint behavior for precast column. Test failure modes were accurately predicted by the calibrated FE models. Numerical parameters for contact surface were identified for the joint analysis. Abstract: The seismic performance of the novel precast concrete frame with mechanical joints using metal plates proposed to provide moment connections was estimated by the numerical analysis verified by experimental investigations. Nonlinear finite element analyses of mechanical column-to-column joints with metal filler plates under static loadings were performed to determine their failure modes and deformations in the column plates. Damages to the proposed novel mechanical connections for composite precast columns using metal plates that create a rigid joint were also elicited. This study also identified the material parameters of the damaged concrete using a plasticity model that were suitable for the prediction of the proposed precast columns. The calibrated dilation angle and concrete damage factor were validated by experimental investigations of the specimens subjected to cyclic loadings; the required stiffness of the column metal plates for rigid joints was identified. A comparison between numerical and experimental results showed that the calibrated FE models accurately predicted the joint behavior of the mechanical column-column joint. Recommendations were made for the practical and optimal design of the mechanical column connections based on the nonlinear behavior of the joints.